Highly selective environmental sensors based on flame-spray-made SnO2nanoparticles - C. Liewhiran (2018)
Flame-spray-made SnO2thick films fabricated by spin coating method were studied for toxic and flammable gas-sensing applications. From physical characterization by X-ray diffraction, Brunauer-Emmett-Teller analysis, scanning and transmission electron microscopy, SnO2nanoparticles were found to have non-agglomerated spherical, hexagonal, rectangle (3-10 nm), and rod-like (3-5 nm in width and 5-20 nm in length) morphologies with large specific surface area of 141.6 m2/g. The sensing films were prepared by spin coating on Al2O3substrate with interdigitated Au electrode. The sensing films were tested toward some important toxic (NO2, CO, SO2) and flammable (H2, C2H2) gases. It was found that SnO2sensing film showed excellent response and selectivity for NO2at a low operating temperature of 200 °C. In addition, the response linearly increased and the response time drastically decreased with increasing gas concentration. Therefore, the spin-coated flame-spray-prepared SnO2sensor is one of the most promising candidates for highly sensitive and selective detection of noxious NO2gas. © 2012 Elsevier B.V. All rights reserved.